y=60-4x

Simple and best practice solution for y=60-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=60-4x equation:


Simplifying
y = 60 + -4x

Solving
y = 60 + -4x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying
y = 60 + -4x

See similar equations:

| 6a-5c=-7 | | 3*(x+3)-1=2 | | 6Y-3-3Y=78 | | 7(M-3)-5=20-2(M-13) | | 2X-3(3X-9)=4(-2X+8) | | 2X-3=9+4X | | Z-17.2=17.3 | | s-17=1(s-5) | | 2X+3X-7+2=35-5X | | 12Y+48=7Y-47 | | 8x+14=x-16 | | 6y+7-2y+5=40 | | 8x-5+3x=28 | | 5(x+2)=6(x-1) | | 7x+21=4x-12 | | 8-3y=-11 | | 2(1-5x)+3(-1-x)-4(-7+2x)=-x | | 3x-4=65 | | 4x-2=x+15 | | 5x^2-35x+75=13 | | -6x+3=300 | | (1+3x)-(1-2)+(-11-7x)=5 | | 7n-21=28 | | 2h+14=20 | | x-(-4)=18 | | 2x+1/3=12/3-2x | | (2x+6y)+(4x-y)= | | 2x+6y+4x-y= | | 4x+3x=54 | | Y=4x+cwhatisy | | 6a+ab=0 | | (3)+0.7(3)=2.4+0.9(3) |

Equations solver categories